A Modern View of the Interstitial Space in Health and Disease - Stewart, Randolph H. (Frontiers in Veterinary Science, 2020)
Increases in the volume of the interstitial space are readily recognized clinically as interstitial edema formation in the loose connective tissue of skin, mucosa and lung. However, the contents and the hydrostatic pressure of this interstitial fluid can be very difficult to determine even in experimental settings. These difficulties have long obscured what we are beginning to appreciate is a dynamic milieu that is subject to both intrinsic and extrinsic regulation. This review examines current concepts regarding regulation of interstitial volume, pressure and flow and utilizes that background to address topics of interest that impact IV fluid administration. These topics include the role of the interstitium in whole body sodium regulation, the link between hypotensive shock and multiple organ dysfunction syndrome and the non-intuitive effect of inflammation on interstitial hydrostatic pressure.